2009
DOI: 10.1159/000265938
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Outcomes of ‘Voluntary’ and ‘Quasi-Compulsory’ Treatment of Substance Dependence in Europe

Abstract: Aim: This study evaluates quasi-compulsory drug treatment (QCT) arrangements for substance-dependent offenders receiving treatment instead of imprisonment in comparison to voluntary treatment within five European countries. Methods: Participants were interviewed with the European Addiction Severity Index, the ASI-crime module, questions on perception of pressure and self-efficacy, and the Readiness-to-Change Questionnaire at treatment entry and after 6, 12, and 18 months. Results: Reductions in substance use a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 74 publications
1
18
0
3
Order By: Relevance
“…Services from the United Kingdom, Italy, Austria, Germany, and Switzerland were selected if they treated participants eligible for either QCT or voluntary groups [4,25] . The QCT group was defined as participants receiving treatment on court order (i.e.…”
Section: Services and Participant Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Services from the United Kingdom, Italy, Austria, Germany, and Switzerland were selected if they treated participants eligible for either QCT or voluntary groups [4,25] . The QCT group was defined as participants receiving treatment on court order (i.e.…”
Section: Services and Participant Selectionmentioning
confidence: 99%
“…In a recent study, we demonstrated that treatment of such offenders reduces substance use and crime and improves health and social integration similarly to voluntary treatment [4] . However, at present only a few substance-dependence treatment programmes for prisoners are available (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…It also implies that dependent drug users should receive no automatic exemption from punishment for any other crimes that they commit, as they retain responsibility for their actions. If they do commit such crimes, then offering them a treatment alternative to an otherwise justified criminal sanction may offer a way to limit the infliction of penal pain whilst also more effectively protecting potential victims from future offences (Schaub et al, 2010;Stevens, McSweeney, van Ooyen, & Uchtenhagen, 2005).…”
Section: Do 'Addicts' Lose Rights?mentioning
confidence: 99%
“…If he or she is not granted the right to withdraw consent, this court order is a form of CCC, but if he or she has the full right to withdraw consent at any time, it is not. The latter situation, when the person has the legal right to withdraw consent and leave treatment, is sometimes called ‘quasi-compulsory treatment’, due to the constrained choice when the only alternative to treatment is prison [14,15]. The orders from drug courts include not only residential treatment, but also placement in outpatient programs.…”
Section: Introductionmentioning
confidence: 99%